KEBIJAKAN PENANGGULANGAN GELANDANGAN DAN PENGEMIS (GEPENG) - Mustofa, Mustofa; Yuliani, Febri; R.F.S, Harapan Tua (Jurnal Ilmu Administrasi Negara, 2018)
Policy Prevention of Homeless and Beggars. The purpose of this research is policy prevention of homelessness and beggars in the City of Kuala Tungkal, West Tanjung Jabung Regency, Jambi Province. This research uses qualitative descriptive research method approach. Primary data obtained directly through interviews from key informen, namely the head of Social Services, Social Rehabilitation and Social Security, Social Security, Gepeng. The secondary data is obtained from the research document. Data analysis techniques begin by collecting data, presenting data, and drawing conclusions. The results of this study indicate that the policy of prevention of homeless and beggars in the City of Kuala Tungkal has not been implemented properly. Shortcomings in the implementation of the policy of prevention of homeless and beggars at this time is still a lack of supervision conducted from the Social Service.